BRAFV600E Mutation Does Not Significantly Affect the Efficacy of Radioiodine Therapy in Patients With Papillary Thyroid Carcinoma Without Known Distant Metastases. (July 2018) - Shen, Guohua; Kou, Ying; Liu, Bin; Huang, Rui; Kuang, Anren
Abstract : Purpose: The BRAF V600E mutation is the most common and specific oncogenic event in papillary thyroid carcinoma (PTC). However, its role in radioiodine therapy decision making has yet to be established. This study aimed to evaluate the impact of the BRAF V600E mutation on the clinical response to radioiodine therapy. Methods: This retrospective study included PTC patients who received total thyroidectomy with lymph node dissection, radioiodine therapy, and thyroid-stimulating hormone suppression between January 2012 and March 2016. Included patients were divided into 2 groups based on the BRAF mutation status. The association between the clinicopathological characteristics and the BRAF V600E mutation was evaluated. After a median follow-up of 37 months, the clinical outcome between these 2 groups was also compared based on the ongoing risk stratification. Results: A total of 512 PTC patients without distant metastases were included, with a positive BRAF mutation in 338 patients. No significant association was observed between the BRAF mutation and clinicopathological characteristics, except for sex, tumor size, and extrathyroidal extension. The initial risk stratification between the positive and negative mutation groups revealed no significant difference ( P = 0.845). At the end of follow-up, no significant difference regarding the clinical response to radioiodine therapy was demonstrated between these 2 groups for all patients or patients with high recurrence risk ( P = 0.586 and P = 0.680, respectively). Conclusions: The BRAF V600E mutation status may not impact the clinical response to radioiodine therapy for PTC patients without distant metastases.